A review of the Nearctic linyphiid spider Arcuphantes fragilis (Araneae, Linyphiidae) and closely related species - Ma, Shuangchun; Marusik, Yuri M.; Tu, Lihong (Zootaxa, 2016)
The Western Nearctic species Arcuphantes fragilis Chamberlin & Ivie, 1943 and several closely related species are reviewed. Seven species are recognized, including two new species: A. cavaticus Chamberlin & Ivie, 1943, A. decoratus Chamberlin & Ivie, 1943, A. fragilis Chamberlin & Ivie, 1943, A. dentatus n. sp., A. curvomarginatus n. sp., A. potteri Chamberlin & Ivie, 1943, and A. sylvaticus Chamberlin & Ivie, 1943. The female of A. decoratus is described for the first time. These seven species share a same genital type, distinguishing them from other congeners, with small differences among them. Illustrations for A. dentatus n. sp., SEM images and digital photographs for all seven species are presented. Descriptions of new species, redescriptions of known species and a key for the seven species are provided.